Соціально-економічна характеристика селянства Харківської губернії напередодні української революції 1917-1921 років - Мотенко, Ярослав Володимирович; Шишкіна, Євгенія Костянтинівна (НТУ "ХПІ", 2015)
Пропонована стаття є результатом комплексного дослідження виробничих відносин у аграрній сфері Харківської губернії напередодні Української революції 1917–1921 років. Автори розкривають зв’язок специфіки розвитку сільськогосподарського сектору економіки Харківщини з виникненням місцевого селянського руху. Головними наслідками ринкової трансформації економіки регіону на початку ХХ ст. стало дистанціювання селян, які поєднували працю у сільському господарстві із заробітками у промисловості, від проблем землеробства і становлення господарств фермерського типу. Показано, що погіршення внутрішньоекономічної ситуації в країні внаслідок Першої світової війни посилило прагнення селянства до примусового перерозподілу землі.

The given article presents results of complex analysis of agrarian sphere productive relations in the Kharkiv guberniya on the eve of Ukrainian revolution of 1917–1921. The authors show the connection of Kharkiv agrarian sector development and local peasant movement origin. In the paper is emphasised that the main consequence of market transformations in the region economy of the early 20th century was peasants (working both in agriculture and industry) staying away of agricultural problems and farming economy creation. Stolypin agrarian reform played a progressive role in the development of guberniya agricultural industry; nevertheless it provoked the common land alienation conflict between peasant village communities and individual farmsteads. Peasant population overflow and agrotechnological backwardness problems remained undetermined. Most peasants low educational level didn’t allow them to understand extensive production non-prospectivety therefore the myth of leveling guberniya land redistribution as the most effective agrarian progress feature stayed persistent idea in the peasant population consciousness. The worsening of state domestic economic conditions in consequence of the Fist World War strengthened peasants’ aspiration for the forced land redistribution.
Social and economic characteristic of Kharkiv Guberniya Peasants on the eve of Ukrainian revolution of 1917–1921
Keywords: аграрна реформа; земельне питання; селянський рух; землеробство; land question; peasant movement